ANALISIS FITUR DASAR RESOR TERHADAP KEPUASAN PENGUNJUNG DI BUMI KATULAMPA RESORT KABUPATEN BOGOR: Analysis Of Basic Resort Features On Visitor Satisfaction At Bumi Katulampa Resort, Bogor District - Rima Pratiwi Batubara; Rini Untari; Saleha; Aditya Sugih Setiawan (Bogor Hospitality Journal, 2024)
The research was conducted to determine the basic resort feature components at Bumi Katulampa Resort & Convention. The results of the research can be used by managers as a management plan in the future so that aspects that become improvements for managers in managing their resorts are known. This research is qualitative in nature with the sample being resort users. Data were analyzed using qualitative descriptive analysis. The results of the study, namely on the nuances of the resort, it is known that the resort has serenity, changes in lifestyle, and opportunities for relaxation. The accuracy of the information is very clear. The condition of the property has a concept on the unification of nature and local culture. Property facilities are considered to have no significant use of technology. Geographical location is on the outskirts of the city. The resort's reputation is good for its authentic portrayal of nature and local culture. Recreation services in the form of indoor and outdoor recreation. Resorts tend to provide recreational value. Food and beverage service is carried out in a buffet service. The results of the analysis of basic resort features can be used as a reference for tourism managers in planning the budget for fulfilling tourism products so that it is hoped that the products offered are in accordance with the needs and desires of tourists without having to eliminate the image of the manager that they want to create